Public Policies on the Socioeconomic Effects of Migration - Ezgim Yavuz; Nazan Susam (İstanbul İktisat Dergisi)
To develop a public policy, it is important to understand the experiences of forced migrants. This study reveals the effects of forced migration on public finances in countries hosting displaced people. In this context, public policy support for access to basic humanitarian needs such as education and health, which are semi-public goods, will be evaluated through a quantitative analysis. Interviews with refugees within the scope of this research draw a picture of the current situation. Thus, evaluating the effectiveness and shortcomings of existing policies and determining the policy support needed are among the unique values of this research. Since migration is a dynamic process, it is also aimed to provide a basis for future studies in this field and to reveal the current situation.